Reassessing the Demography Hypothesis: the Great Brazilian Crime Shift - Jo\~ao M. P. De Mello (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2010)
Mimicking the US in 1980 and 1990s, Brazil is a remarkable case of a major shift in homicides. After increasing steadily throughout the 1990s and the beginning of the 2000s, homicides reached a peak in 2003, and then fell. I show a strong time-series co-movement between homicide rates and the percentage of the population in 15-24 age bracket. Using a panel of states, I find a very high elasticity of homicide with respect to changes in the 15-24 year-old population (2.4), after controlling for income, income inequality, and state and year fixed effects. I then focus on the case of S\~ao Paulo, the largest state in the country, and whose shift in homicides has been particularly acute. City-level panel elasticities are similar to the state-level estimates. Furthermore, the demographic shift in S\~ao Paulo was more pronounced than the national one, explaining the particularly large shift in homicides in S\~ao Paulo. The large cohort born from the mid 1970 through the early 1980 is the result of a sharp reduction in infant mortality only belatedly followed by acceleration in the reduction of fertility. In line with the Easterlin Hypothesis (Easterlin [1980]), this large cohort faced tough economic conditions. Educational attainment ceased to improve for this cohort, and unemployment rates upon entering the job market were exceptionally high. Thus, the large homicide shift in Brazil is produced by a particularly large and socially fragile cohort.
Keywords: 330; Age Structure; Demographic Change; Homicides; Altersstruktur; Bevölkerungsentwicklung; Suizid; Brasilien